If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7 = 4x + -67 Reorder the terms: 7 + 2x = 4x + -67 Reorder the terms: 7 + 2x = -67 + 4x Solving 7 + 2x = -67 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 7 + 2x + -4x = -67 + 4x + -4x Combine like terms: 2x + -4x = -2x 7 + -2x = -67 + 4x + -4x Combine like terms: 4x + -4x = 0 7 + -2x = -67 + 0 7 + -2x = -67 Add '-7' to each side of the equation. 7 + -7 + -2x = -67 + -7 Combine like terms: 7 + -7 = 0 0 + -2x = -67 + -7 -2x = -67 + -7 Combine like terms: -67 + -7 = -74 -2x = -74 Divide each side by '-2'. x = 37 Simplifying x = 37
| V-9+6=9 | | n-5.41=3.75 | | -5x+4(2x-12)=-18 | | 3/131/4 | | 14x^3-35x^2+28x= | | -2x(5x+8)= | | 3w^2-20w-25=0 | | K+12-6k=-27k | | 2x+7=2x-67 | | 9x+17+3x+19=180 | | 8x-8=-8x+24 | | -3(x-5)=3(5-x) | | 2x+7=1x+9 | | 10/m=5/11 | | 32=4+6x | | 4j+j= | | x-2=2x-91 | | N-5+4=8 | | 2x+2=11-x | | 1/4/12=n | | 2(c+7.2)=3.2 | | 18x-4=58+10x-8 | | -5+4y= | | x+78=2x-14 | | 2z=-1/2 | | -2x(5x+3)= | | 9*n+6=18 | | 5+(-11)+14= | | 2x=-(3y+1) | | (H/6)-2=15 | | 7(7x+4)+1=78 | | 3r+2=2r+2 |